2021
DOI: 10.1002/ange.202012046
|View full text |Cite
|
Sign up to set email alerts
|

Histone H4 Tails in Nucleosomes: a Fuzzy Interaction with DNA

Abstract: The interaction of positively charged N‐terminal histone tails with nucleosomal DNA plays an important role in chromatin assembly and regulation, modulating their susceptibility to post‐translational modifications and recognition by chromatin‐binding proteins. Here, we report residue‐specific 15N NMR relaxation rates for histone H4 tails in reconstituted nucleosomes. These data indicate that H4 tails are strongly dynamically disordered, albeit with reduced conformational flexibility compared to a free peptide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 80 publications
1
6
0
Order By: Relevance
“…1a ). Consistent with previous studies 41,42 we observed resonances for only 15 of the 101 non-proline amino-acids of full length H4, corresponding to tail residues 1-15 ( Fig. 3c ).…”
Section: Bptf Phd-bd Demonstrates Restricted Specificity and Synergis...supporting
confidence: 92%
See 1 more Smart Citation
“…1a ). Consistent with previous studies 41,42 we observed resonances for only 15 of the 101 non-proline amino-acids of full length H4, corresponding to tail residues 1-15 ( Fig. 3c ).…”
Section: Bptf Phd-bd Demonstrates Restricted Specificity and Synergis...supporting
confidence: 92%
“…1 - 2 ). The H4 tail is K/R-rich, has decreased dynamics in the nucleosome vs. peptide context, and computational models suggest it may also form a fuzzy complex with DNA 41 . To further characterize H4 tail conformation in the Nuc environment, we utilized NMR spectroscopy to investigate a Nuc containing 15 N-H4 (see Methods ).…”
Section: Bptf Phd-bd Demonstrates Restricted Specificity and Synergis...mentioning
confidence: 99%
“…The reactivity of AP sites upon histone tails removal is decreased, 11 yet there are strong interactions already in this scenario, which opens very interesting perspective towards the study of full length histone tails interactions with AP sites in NCPs. We hone a robust methodology for modeling full length histone tails, which is a timely line of research 35 as the community would benefit from extensive benchmarks to identify force fields able to accurately represent such complex combination of ordered and disordered assemblies. The combination of enhanced sampling methods and machine learning algorithms can also be explored to correctly sample the highly complex conformational landscape of the full-length disordered tails, and gives promising openings towards further studies.…”
Section: Extrahelicity Of the Lesion Sites (%)mentioning
confidence: 99%
“…Nucleosome core particles (NCPs), the basic units of eukaryotic chromatin, consist of 145–147 bp of DNA wrapped ∼1.6 to 1.7 times around an octameric core of histone proteins (H2A, H2B, H3, and H4). The N-terminal histone tails are highly positively charged and rich in arginine and lysine that are important for nucleosome stability. Internucleosomal interactions between the N-terminal histone H4 tail and H2A/H2B acidic patch affect the overall structure of chromatin. , In addition, histone tails impact crucial interactions with nucleosome-binding proteins through direct contact and by modulating the accessibility of nucleosomal DNA. , Post-translational modifications (PTMs) and oncohistone mutations on histone tails that change the effective positive charge, such as lysine acetylation and Arg to Ala mutations, further complicate nucleosome dynamics, chromatin compaction, and the interactions of chromatin-associated proteins with DNA. , Despite the importance of electrostatic interactions, there is a gap in our knowledge concerning the effects of histone tails on the local ionic environment of the nucleic acids.…”
Section: Introductionmentioning
confidence: 99%